Determination of Potassium Bromate in Bread Brands in Sulaimani City, Kurdistan-Iraq - Abdullah Ahmed Hama; Sardar M. Weli; Sabiha M Salih; Ary B. Feaq; Fatima M. Ali (UHD Journal of Science and Technology, 2022)
Bread is the most consumed and staple food in many countries worldwide. It is made from dough of flour such as wheat and barley, and water. It usually contains flour improver potassium bromate (KBrO3) which is used by bakers. However, many studies have confirmed the deleterious effects of KBrO3 on human health. Therefore, this study aimed to determine the rate of KBrO3 in five main types of bread in Sulaimani city, Kurdistan-Iraq. The duration of the study was from August 2021 to November 2021. Thirty bread samples were collected from five main products that are extremely consumed by Kurdish citizens. The bread-type products were bakery bread (Nani frn), white hamburger bread (Samun), white bread known as Kurdish bread (Nani Hawrami), pizza, and brown barley bread. Single beam UV–visible spectrophotometer APEL-303 was used for the quantification of KBrO3 in bread samples. The results found that all 30 samples were had KBrO3 residues in their products with different concentrations. Samples of brown barley bread were having the least content of KBrO3 while samples from pizza dough were having the highest concentration of KBrO3. The present study concludes that all bread samples from five major bread types had potassium bromate above the permitted levels allowed by the United States Food and Drug Agency (FDA).